Efficacy Of Montelukast As A Therapeutic Option In Bronchiolitis - Akhtar, Zohaib; Iqbal, Amjad; Sabir, Sajjad; Aslam, Sohail; Aslam, Muhammad Shahid; Iqbal, Tahreem (Journal of Rawalpindi Medical College, 2025)
OBJECTIVE: To determine the efficacy of Montelukast as a therapeutic option in treating bronchiolitis and establish a relationship between Montelukast and clinical outcomes in our children with acute bronchiolitis. PATIENTS AND METHODS: A descriptive cross-sectional study was conducted at Combined Military Hospital, Abbottabad, from September 2024 to November 2024. Infants with bronchiolitis between the ages of 1 and 2 years were included in the study. Group A consisted of those with a history of prior montelukast use for more than two weeks before acute bronchiolitis, and Group B consisted of those who did not. Data was collected using a pre-designed form filled by paediatric residents. Relevant demographic and clinical data regarding various risk factors were recorded. RESULTS: A total of 230 children with bronchiolitis. The mean age of participants was 15.97 ±3.431 months. 74 (32.2%) patients had a history of prior montelukast ingestion, and 142 (61.7%) were categorised as low risk as per the clinical severity scale (CSS). Pearson Chi-square test revealed that CSS, oxygen saturations and need for Continuous Positive Airway Pressure (CPAP) differed significantly between group A and group B. P- value was 0.040, 0.050 and 0.020, respectively. CONCLUSION: Most children had low CSS scores at this age. Those with a prior history of montelukast ingestion were less likely to desaturate, require CPAP or have a higher CSS score. KEY WORDS: Bronchiolitis, infant, montelukast, oxygen saturation, nasal continuous positive airway pressure, length of stay.